Student Ethics in Classical Texts: A Comparative Study of Ta’lim al-Muta’allim and Serat Wulangreh - Halintar Shah Reza Effendi Zaqlul Faza M.E; Sugiyo; A. Dardiri Hasyim (Edumaspul: Jurnal Pendidikan, 2026)
This study aimed to analyze the concept of student ethics in Ta’lim al-Muta’allim by Imam al-Zarnūjī and Serat Wulangreh by Pakubuwana IV, and to examine their implementation and relevance in Islamic boarding school education in the global era. This study employed a qualitative approach using library research and a case study at Nurul Qur’an Islamic Boarding School, Boyolali. Data were collected through document analysis, observation, and interviews, while data analysis used hermeneutic interpretation and descriptive analytical methods with triangulation to ensure validity. The results showed that both texts emphasized sincerity of intention, respect for teachers, discipline, humility, and self-control in the learning process. These values were implemented through integration into the curriculum and institutional culture of the pesantren. Furthermore, the concept of student ethics in both texts remained relevant in addressing contemporary educational challenges such as moral decline, digital ethics, and academic dishonesty. Therefore, these classical texts could serve as a strong foundation for strengthening character education in the global era.